Analysis of Perinatal Mortality in Baixada Maranhense between the years from 2018 to 2021 (Research, Society and Development, 2022)
Introduction: Infant Mortality (IM) represents an important indicator of the quality of health and socioeconomic development of a population. According to the World Health Organization (WHO) , universal health coverage highlights the importance of IM for approaching the health conditions of populations, as well as its potential to guide health policies and actions. Objective: To identify the Perinatal Mortality Analysis in Baixada Maranhense between the years 2018 to 2021. Method: Bibliographic descriptive epidemiological study research, with the purpose of collecting data from SIM and SINASC, variables related to the NB will be used to describe the data. (birth weight, gestational week, type of delivery and perinatal deaths according to ICD -10) to obtain answers to the general objective of this study. Results: According to the data collected during the research, in the years 2018 to 2020, the mortality rate in children with diarrhea grew unreasonably according to data collected and presented in the form of graphs, demonstrating that the highest perinatal deaths during the year 2021 were in the municipalities of Viana, Pinheiro and Penalva in the births will take place in their homes. Final Considerations: The data presented in the Information System on Live Births, especially SINASC, were the main tool for the development of this work, so that the rates of deaths during childbirth and infant mortality could be quantified.